ON ARCHAEOCYATH COLLECTIONS HOUSED AT THE PALEONTOLOGICAL INSTITUTE OF THE RUSSIAN ACADEMY OF SCIENCES - Zhuravlev A. (My University, 2001)
The collection numbers of A.G. Vologdin, A.N. Vlasov, Yu.I. Voronin, K.N. Konjuschkov, and V.I. Yaworski on archaeocyaths and certain other Vendian and Cambrian fossils, which were transferred to the Stock Division of the Paleontological Institute of the Russian Academy of Sciences, are listed. Some of these collections were thought to be lost. The name-bearing types are established in the type series.
Keywords: Archaeocyath; Cambrian; Vendian; Палеозой::Кембрийская; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский